Towards the Ontology of Places in Poland: an Example of the Mazowieckie Voivodship - Krzysztof Pancerz; Piotr Grochowalski; Aneta Derkacz (Barometr Regionalny, 2016)
The main goal of our research is to build the ontology of places in Poland covering variety of aspects of places, mainly administrative and socio-economic. In the paper, we show a part of the ontology on the example of the Mazowieckie Voivodship. The ontology is being implemented using the OWL 2 Web Ontology Language.